Нові дослідження граветської стоянки Троянове 4 на Кіровоградщині у 2007 р. - Залізняк, Л.Л.; Вєтров, Д.О. (Археологічні дослідження в Україні, 2009)
The article is devoted to the publication of materials from a new research in 2007 at the first in the Central Ukraine Gravettian settlement Troyanove 4.